1994
DOI: 10.1021/tx00037a004
|View full text |Cite
|
Sign up to set email alerts
|

An o-quinone form of estrogen produces free radicals in human breast cancer cells: Correlation with DNA damage

Abstract: The o-quinone forms of 2,3- and 3,4-catechol estrogens have been implicated in the carcinogenicity of these hormones. The concomitant production of reactive oxygen species during reduction of the o-quinone estrogens has been inferred to play a mechanistic role in their mutagenic potential. Conclusive evidence documenting the production of hydrogen peroxide, the hydroxyl radical, and the estrone 3,4-semiquinone in estrone 3,4-quinone (3,4-EQ)-treated human breast cancer subcellular fractions was demonstrated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(90 citation statements)
references
References 14 publications
3
87
0
Order By: Relevance
“…The origin of this excess H 2 O 2 in tissue is principally O 2 •− (see Fig. 1) and involves the enzyme superoxide dismutase (SOD) [4,6,12]. The prooxidant effect of 3,4-E1Q was especially profound in the uterus homogenate of ovariectomized animals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The origin of this excess H 2 O 2 in tissue is principally O 2 •− (see Fig. 1) and involves the enzyme superoxide dismutase (SOD) [4,6,12]. The prooxidant effect of 3,4-E1Q was especially profound in the uterus homogenate of ovariectomized animals.…”
Section: Discussionmentioning
confidence: 99%
“…H 2 O 2 production in tissues was determined using the method described Nutter et al [12] with some modifications [10]. Briefly, brain, liver, retina and uterus homogenates (0.2% w/v in 0.1M PBS, pH 7.4, final volume of 100 μL) were incubated without and with E2 or the estrogen derivatives (100 μM), NADPH (200 μM) and sodium azide (20 μM) at 37°C for 30 minutes in a shaking water bath.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prooxidant activity of 1 and 2 in OVX brain homogenate was evaluated according to a previously published method based on the production of H 2 O 2 production at 37 °C [33]. Briefly, in brain homogenate (0.2% w/v in 0.1M PBS, pH 7.4, final volume of 100 µL) 100 µM test compounds 1, 2 or 3,4-ortho-quinone of estrone as positive control, NAD(P)H (200 µM) and sodium azide (20 µM) at 37°C for 30 minutes in a shaking water bath.…”
Section: Induction Of Hydrogen Peroxide Productionmentioning
confidence: 99%
“…Such redox cycling is believed to be responsible, in part, for the carcinogenicity of estrogens [45]. The profoundly prooxidant estrone-3,4-quinone [33] was used as positive control in this experimental paradigm. The measured hydrogen peroxide production (given in nmol·h −1 · mg protein −1 ) in OVX rat brain homogenate clearly showed that the para-quinol to phenol (2→1) conversion does not produce oxidative stress compared to that of the control, while estrone-3,4-quinone produced approximately a 5-fold increase in H 2 O 2 production (Fig.…”
Section: Hydrogen Peroxide Productionmentioning
confidence: 99%